2008
DOI: 10.1590/s0102-33062008000100023
|View full text |Cite
|
Sign up to set email alerts
|

Análise estrutural de folhas de Eugenia uniflora L. (Myrtaceae) coletadas em ambientes rural e urbano, SP, Brasil

Abstract: São Paulo, diferem quanto à estrutura foliar, de exemplares encontrados em área rural, isenta de poluentes aéreos urbanos. Foram avaliadas, comparativamente, as dimensões da folha e, em microscopia de luz, a espessura dos tecidos foliares, a densidade de estômatos e de cristais da espécie, coletada em área rural e em dois pontos da cidade de São Paulo: canteiro central da Avenida dos Bandeirantes, com tráfego veicular intenso, portanto com alta carga de poluentes primários, e no Parque Estadual das Fontes do I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 25 publications
(19 reference statements)
3
26
1
14
Order By: Relevance
“…In comparison to other members of Eugenia, in general, there are some anatomical similarities among the leaves, such as stomata restricted to the abaxial surface, a striated cuticle, polygonal epidermal cells that are wavy in surface view, dorsiventral mesophyll, a midrib with a bicollateral vascular bundle in an open arc that is surrounded by a sclerenchymatic sheath, secretory cavities that mostly occur in the subepidermis, druses and prismatic crystals of calcium oxalate and phenolic compounds (Fontenelle et al, 1994;Lorca et al, 1995;Jorge et al, 2000;Medeiros, 2000;Donato & Morretes, 2007;Alves et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to other members of Eugenia, in general, there are some anatomical similarities among the leaves, such as stomata restricted to the abaxial surface, a striated cuticle, polygonal epidermal cells that are wavy in surface view, dorsiventral mesophyll, a midrib with a bicollateral vascular bundle in an open arc that is surrounded by a sclerenchymatic sheath, secretory cavities that mostly occur in the subepidermis, druses and prismatic crystals of calcium oxalate and phenolic compounds (Fontenelle et al, 1994;Lorca et al, 1995;Jorge et al, 2000;Medeiros, 2000;Donato & Morretes, 2007;Alves et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Alves et al (2008) demonstrated that the dimensions of the leaves of E. uniflora vary between plants that grow in urban and rural environments. The pollutants of cities can be responsible for the smaller leaves, higher proportion of palisade parenchyma, reduction of intercellular spaces, higher density of stomata and higher amount of crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Fares et al (2006) reported reduced leaf size of Populus alba L. indirectly exposed to ozone. Alves et al (2008) found a significant decrease in the leaf length and width of E. uniflora in plants exposed to heavy traffic areas, with great loads of particulate matter and primary pollutants (sulfur dioxide, nitrogen oxides, carbon monoxide) in São Paulo, Brazil. These findings showed that under polluted environments plants invest less in increasing leaf area.…”
Section: Discussionmentioning
confidence: 91%
“…Kuntze (Araucariaceae), por Mazzoni-Viveiros e Trufem (2004) [34] com Tibouchina pulchra Cogn. (Melastomataceae) e por Alves, Tresmondi e Longui (2008) [2] com Eugenia uniflora L. (Myrtaceae).…”
Section: Introductionunclassified